1994
DOI: 10.1007/bf00197549
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin inhibits proliferation of human breast cancer cell lines

Abstract: In this study we show that treatment of MDA-MB231 hormone-independent human breast cancer cells with oxytocin (OT) or with the OT analogue F314 induces significant growth inhibition together with a change in cell phenotype. In MCF7 and T47D human breast cancer cells, OT inhibits oestrogen-induced cell growth. In these same cells, OT administration significantly enhances the inhibitory effect of tamoxifen on cell proliferation. MDA-MB231, MCF7 and T47D cells all express mRNA specific for the OT receptor. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 22 publications
5
73
0
1
Order By: Relevance
“…Oxytocin, produced during pregnancy, delivery and breastfeeding, may have a role in the control of mammary cell growth [29] and inhibiting proliferation of human BCa cells, which may offer BCa prevention and treatment [30]. These findings have driven a hypothesis that oxytocin may have therapeutic effects on cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin, produced during pregnancy, delivery and breastfeeding, may have a role in the control of mammary cell growth [29] and inhibiting proliferation of human BCa cells, which may offer BCa prevention and treatment [30]. These findings have driven a hypothesis that oxytocin may have therapeutic effects on cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, in vitro effects of OT on cell proliferation vary from antiproliferative to mitogenic (26,28,47,48). In choriocarcinoma, OT promotes cell growth (30), whereas it decreases proliferation of glial tumors, endometrial adenocarcinomas, and neuroblastomas (23,27).…”
Section: Discussionmentioning
confidence: 99%
“…All of the cells were grown as monolayers in RPMI medium (Gibco, Paisley, Scotland) with 10% fetal calf serum (Gibco) in 25 cm 2 T flasks in a 5% CO 2 humidified atmosphere at 371C. Previous experiments have shown that MCF7, MOG-U-V-W and TS/A cells are OTR positive (Cassoni et al, 1994(Cassoni et al, , 1998; the KATO cells acted as an OTR-negative control.…”
Section: Binding Studies On Tumour Cellsmentioning
confidence: 99%
“…The oxytocin (OT) hypothalamic nonapeptide binds to various tumour types via the oxytocin receptor (OTR), a member of the seven transmembrane spanning family of G-protein-coupled receptors (Kimura et al, 1992;Gimpl and Fahrenholz, 2001). The tumoral expression of OTRs was first described in human breast cancer cell lines (Cassoni et al, 1994) and a large percentage of primary breast cancers (Bussolati et al, 1996). OTRs have recently also been detected in tumours of the nervous system such as neuroblastomas and glioblastomas (Cassoni et al, 1998), osteosarcomas (Novak et al, 2000), chorioncarcinomas , small cell lung carcinomas (Pequeux et al, 2002) and Kaposi sarcomas .…”
mentioning
confidence: 99%